Effect of Month of Birth on the Risk of Developing Psoriasis - Martins, Ana (2018)
Introduction: Psoriasis is an immunemediated dermatosis characterized by chronic inflammation, abnormal proliferation and aberrant differentiation of keratinocytes, hyperplastic blood vessels and infiltration of inflammatory cells. Psoriasis is a multifactorial disease and is influenced by genetics and epigenetic modifications that can be triggered by environmental factors. Climate and sun exposure may affect psoriasis prevalence and the ultraviolet radiation is a useful treatment. Our objective was to evaluate the relationship between the month of birth and the risk of developing psoriasis.Methods: The monthly distribution of births of patients with psoriasis (n = 755) was compared to that of a control population, comprised by Portuguese individual born during the same period and from the same region (n = 6 560 032).Results: Birth rate of psoriasis patients decreased in October (OR 0.74; 95% CI 0.55 – 0.99; p 0.041). After Bonferroni correction and after grouping the months by trimesters, no statistical significant differences were found.Conclusion: Our results may be related to the particular meteorological characteristics of Portugal that may lead to stabilization of the vitamin D synthesis during the whole year. The perception of the environmental influence on the development of a specific pathology is very important because it allows the establishment of preventive measures that will reduce disease incidence.